2019
DOI: 10.1177/1074248419841630
|View full text |Cite
|
Sign up to set email alerts
|

Enteral Tranexamic Acid Decreases Proteolytic Activity in the Heart in Acute Experimental Hemorrhagic Shock

Abstract: The mechanisms for cardiac injury after hemorrhagic shock (HS) are unresolved. We hypothesize that remote organ damage can be caused by uncontrolled pancreatic proteolytic activity, as enteral protease inhibition improves outcomes in experimental HS. Uncontrolled proteolysis in the heart may disrupt cardiac metabolism and adrenergic control with subsequent deleterious outcomes. To test this hypothesis, the heart rate–pressure product (RPP) as an index of myocardial oxygen consumption and the levels of fatty ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…Previous studies from our group demonstrated that enteral TXA has a protective function in the systemic circulation. Injury caused by shock to both the vasculature [17] and the heart [18] is mitigated and adrenergic receptor density in arterial smooth muscle and in the heart is preserved with this treatment and is concordant with the improvements in hemodynamics measured in the present study.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Previous studies from our group demonstrated that enteral TXA has a protective function in the systemic circulation. Injury caused by shock to both the vasculature [17] and the heart [18] is mitigated and adrenergic receptor density in arterial smooth muscle and in the heart is preserved with this treatment and is concordant with the improvements in hemodynamics measured in the present study.…”
Section: Discussionsupporting
confidence: 89%
“…Hemorrhagic shock was induced using a standard fixedpressure Wiggers model, as described in previous studies [17,18]. Briefly, blood was slowly removed (0.5 ml/min) until a target mean arterial blood pressure of 40 mmHg was achieved.…”
Section: Trauma/hemorrhagic Shock (T/hs) Experimental Modelmentioning
confidence: 99%
See 1 more Smart Citation